Effectiveness of topical combination of finasterid and minoxidil in the management of male androgenetic alopesia (systematic review and meta-analysis: Hair density study) - Riyanto, Puguh; Karami, Muhammad Zuldan; Malik, Diah Adriani (Science Midwifery, 2025)
Androgenetic alopecia (AAG) is the most common hair loss problem in men, characterized by miniaturization of hair follicles due to systemic androgens and genetic factors. AAG treatment aims to prevent follicle miniaturization Treatment modalities for AAG include hair transplantation, platelet-rich plasma (PRP), microneedling, and stem cells. Each treatment modality has its benefits and risks. The combination of topical finasteride and topical minoxidil has been shown to improve outcomes in several studies. This study aimed to evaluate the efficacy of topical finasteride compared to topical minoxidil in improving hair density among male AAG patients. A systematic literature search method was conducted using MEDLINE, Embase, AMED, Cochrane Library, Clinicaltrials.gov, Web of Knowledge, Web of Science, and WHO ICTRP with the search terms "topical finasteride and minoxidil" 'AND' "male androgenetic alopecia" 'AND' "male pattern hair loss". The literature search was carried out in accordance with the PRISMA 2009 path. Three RCTs were included in the qualitative synthesis and included in the meta-analysis. The results showed that the overall SMD in hair density was 0.751±0.215 (95% CI: 0.331 – 1.162, p<0.001) in favor of topical finasteride and topical minoxidil combination treatment, suggesting that topical finasteride and topical minoxidil combination had much greater effectiveness than control treatments in improving hair density among male patients with AAG.